An extensive operations and maintenance planning problem with an efficient solution method - Seif, Javad; Yu, Andrew J. (Computers & operations research, 2018)
•A mixed integer program for operations and maintenance planning is introduced.•Multiple maintenance types, maintenance stations and operations are considered.•An exact solution algorithm for the problem is presented.•Computational experiments are presented for performance evaluation of the algorithm.•The algorithm performs efficiently for very large instances of the problem. In this paper, we extend the formulation and solution algorithm of a Flight and Maintenance Planning (FMP) problem to cover a wider range of applications. We consider a general Operations and Maintenance Planning (OMP) case where machines are shared between multiple operation schedules as well as have multiple preventive maintenance activities. In this case, machines have different usage-based intervals and the maintenance duration varies for each machine. We formulate and optimize the OMP problem to accommodate the maintenance requirements and physical characteristics of multiple stations. We evaluate the performance of the generalized solution methodology and show its effectiveness and efficiency through computational experiments.